2019
DOI: 10.1126/sciadv.aaw2880
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic signatures of methylated DNA cytosine in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD), a progressive neurodegenerative disorder, is the most common untreatable form of dementia. Identifying molecular biomarkers that allow early detection remains a key challenge in the diagnosis, treatment, and prognostic evaluation of the disease. Here, we report a novel experimental and analytical model characterizing epigenetic alterations during AD onset and progression. We generated the first integrated base-resolution genome-wide maps of the distribution of 5-methyl-cytosine (5mC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…On the other hand, epigenetic factors, such as adverse environmental cues or aging, may directly reprogram the epigenome, which, in turn, may alter the expression-associated genes to result in neurodegenerative diseases [76]. In our previous study [17], we reported the first genome-wide roadmap of epigenetic signatures in AD based on the methylated DNA base cytosine [17]. Significantly, in the present study, we determined novel FUS-specific AD genes, whose transcriptional alterations were significantly linked to key AD risk factors.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the other hand, epigenetic factors, such as adverse environmental cues or aging, may directly reprogram the epigenome, which, in turn, may alter the expression-associated genes to result in neurodegenerative diseases [76]. In our previous study [17], we reported the first genome-wide roadmap of epigenetic signatures in AD based on the methylated DNA base cytosine [17]. Significantly, in the present study, we determined novel FUS-specific AD genes, whose transcriptional alterations were significantly linked to key AD risk factors.…”
Section: Discussionmentioning
confidence: 86%
“…Oxidative (oxBS-seq) and methylase-assisted bisulfite sequencing (MAB-seq) at single-base-pair resolution were performed as previously described [17]. We performed oxBS-seq and MAB-seq in all cell lines in the AD patient samples reported in this study.…”
Section: Oxidative and Methylase-assisted Bisulfite Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies support the idea that dysregulated DNA methylation/demethylation is linked to many neuronal disorders, including AD onset and progression. However, the relationship between AD and altered 5-mC levels is not known [37]. 5-mC can be further oxidized to 5-hmC, among others, by the TET family of dioxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that DNA methylation at the fifth position of cytosine (5-mC) plays an important role in neuronal gene expression and neural development. Several studies support the idea that dysregulated DNA methylation/demethylation is linked to many neuronal disorders, including AD onset and progression; however, the relationship between AD and altered 5-mC levels is not known [40]. 5-mC can be further oxidized to 5-hmC, among others, by the TET family of dioxygenases.…”
Section: Discussionmentioning
confidence: 99%